Progress of Polycyclic Boron-Doped Molecular Carbons - Yuan, Liuzhong; Wang, Yue; Dou, Chuandong (Organic Materials, 2023)
Molecular carbons, namely molecular cutout of carbon materials, are of importance for understanding accurate structures of carbon allotropes and developing functional π-electron materials. Doping the boron atoms into π-conjugated skeletons of molecular carbons enables the construction of boron-doped molecular carbons (BMCs), further leading to new chemistry and attractive material systems, which are distinct from carbon-based and other heteroatom-doped molecular carbons. Herein, the bottom-up organic synthesis methodologies have been employed to synthesize BMCs that feature the boron atoms at the edge or in the center of π-skeletons. They have not only amazing topological structures and good stability but also intriguing photophysical and electronic properties. Moreover, they have sufficient Lewis acidity and can coordinate with Lewis bases to form Lewis acid–base complexes, which exhibit stimuli-responsive functions. Notably, some of these BMCs can be utilized in the fields of organic reactions, optical and electronic devices, as well as supramolecular chemistry and photothermal materials. In this short review, we aim to highlight the design and synthetic strategies of polycyclic BMCs, and their unique physical properties and practical applications.
Keywords: molecular carbons; boron; electron deficiency; Lewis acidity; topological structures